Transfer studies of polystyrene nanoparticles in the ex vivo human placenta perfusion model: key sources of artifacts. Issue 4 (16th July 2015) - Grafmueller, Stefanie; Manser, Pius; Diener, Liliane; Maurizi, Lionel; Diener, Pierre-André; Hofmann, Heinrich; Jochum, Wolfram; Krug, Harald F.; Buerki-Thurnherr, Tina; von Mandach, Ursula; Wick, Peter
Abstract: Nanotechnology is a rapidly expanding and highly promising new technology with many different fields of application. Consequently, the investigation of engineered nanoparticles in biological systems is steadily increasing. Questions about the safety of such engineered nanoparticles are very important and the most critical subject with regard to the penetration of biological barriers allowing particle distribution throughout the human body. Such translocation studies are technically challenging and many issues have to be considered to obtain meaningful and comparable results. Here we report on the transfer of polystyrene nanoparticles across the human placenta using an ex vivo human placenta perfusion model. We provide an overview of several challenges that can potentially occur in any translocation study in relation to particle size distribution, functionalization and stability of labels. In conclusion, a careful assessment of nanoparticle properties in a physiologically relevant milieu is as challenging and important as the actual study of nanoparticle–cell interactions itself.